Amyloid-β Homeostasis Bridges Inflammation, Synaptic Plasticity Deficits and Cognitive Dysfunction in Multiple Sclerosis - Stampanoni Bassi, Mario; Garofalo, Sara; Marfia, Girolama A.; Gilio, Luana; Simonelli, Ilaria; Finardi, Annamaria; Furlan, Roberto; Sancesario, Giulia M.; Di Giandomenico, Jonny; Storto, Marianna; Mori, Francesco; Centonze, Diego; et al. (Frontiers in Molecular Neuroscience, 2017)
Cognitive deficits are frequently observed in multiple sclerosis (MS), mainly involving processing speed and episodic memory. Both demyelination and grey matter atrophy can contribute to cognitive deficits in MS. In recent years, neuroinflammation is emerging as a new factor influencing clinical course in MS. Inflammatory cytokines induce synaptic dysfunction in MS. Synaptic plasticity occurring within hippocampal structures is considered as one of the basic physiological mechanisms of learning and memory. In experimental models of MS, hippocampal plasticity is profoundly altered by proinflammatory cytokines. Although mechanisms of inflammation-induced hippocampal pathology in MS are not completely understood, alteration of Amyloid-β (Aβ) metabolism is emerging as a key factor linking together inflammation, synaptic plasticity and neurodegeneration in different neurological diseases. We explored the correlation between concentrations of Aβ1-42 and the levels of some proinflammatory and anti-inflammatory cytokines (IL-1β, IL1-ra, IL-8, IL-10, IL-12, TNFα, IFNγ) in the cerebrospinal fluid (CSF) of 103 remitting MS patients. CSF levels of Aβ1-42 were negatively correlated with the proinflammatory cytokine IL-8 and positively correlated with the anti-inflammatory molecules IL-10 and IL-1ra. Other correlations, although noticeable, were either borderline or not significant. Our data show that an imbalance between proinflammatory and anti-inflammatory cytokines may lead to altered Aβ homeostasis, representing a key factor linking together inflammation, synaptic plasticity and cognitive dysfunction in MS. This could be relevant to identify novel therapeutic approaches to hinder the progression of cognitive dysfunction in MS.